2018
DOI: 10.1021/acssuschemeng.8b04990
|View full text |Cite
|
Sign up to set email alerts
|

Critical Review on Sustainable Homogeneous Cellulose Modification: Why Renewability Is Not Enough

Abstract: As we mark the 20 th anniversary after the introduction of the twelve principles of green chemistry, sustainable modification of cellulose, being the most abundant biobased polymer, is worth consideration. Many researchers work on this renewable polymer, however the use of non-sustainable solvents, reactants and modification approaches simply shifts the environmental burden to other stages of the life cycle. Therefore, to achieve true sustainable modification of cellulose, its renewability combined with mild a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
112
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(112 citation statements)
references
References 108 publications
0
112
0
Order By: Relevance
“…Nanocellulose has many interesting, and potentially valuable, properties and is often put forth as a high-performance component candidate in future, sustainable materials, not in the least thanks to their inherent renewability [2,3,4,5,6,7]. Still, renewability is not self-sufficient from a sustainability point of view [36]. Green process conditions are of vital importance and even small improvements, such as a reduction of the energy consumption, substitution of organic solvents with water, and/or the use of efficient catalysts, can have a significant impact on the overall environmental impact of the process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanocellulose has many interesting, and potentially valuable, properties and is often put forth as a high-performance component candidate in future, sustainable materials, not in the least thanks to their inherent renewability [2,3,4,5,6,7]. Still, renewability is not self-sufficient from a sustainability point of view [36]. Green process conditions are of vital importance and even small improvements, such as a reduction of the energy consumption, substitution of organic solvents with water, and/or the use of efficient catalysts, can have a significant impact on the overall environmental impact of the process.…”
Section: Discussionmentioning
confidence: 99%
“…Green process conditions are of vital importance and even small improvements, such as a reduction of the energy consumption, substitution of organic solvents with water, and/or the use of efficient catalysts, can have a significant impact on the overall environmental impact of the process. CNF modification and processing presents a challenge in this respect due to the insolubility in water and with very few sustainable solvent alternatives at hand [36]. Heterogeneous modification is often possible but with less control of yield, degree of substitution, selectivity, and by-products.…”
Section: Discussionmentioning
confidence: 99%
“…The energy requirements, multiple processing steps, and poor atom economy are in direct conflict with the principles of green chemistry and currently preclude this approach as a sustainable solution (Anastas & Warner, 1998; Mendieta, Vallejos, Felissia, Chinga‐Carrasco, & Area, 2020). The production of agropolymers, on the other hand, has considerably improved atom economy and limits the number of necessary chemical transformations but poses its own set of challenges, such as the reliance on heterogeneous or harsh reaction conditions due to inherently poor solubility and high crystallinity of many biopolymers (Bakshi, Selvakumar, Kadirvelu, & Kumar, 2020; Onwukamike, Grelier, Grau, Cramail, & Meier, 2019; Szabo, Gerber‐Lemaire, & Wandrey, 2020; Zhang et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Dissolution in aqueous media is also not desired for any use as cell scaffolding material. 31 P NMR as exemplarily conducted for the hwPHK sample confirmed the expected selective substitution of the primary alcohol groups in C6 position of the anhydroglucose units (data not shown). Previously, we have shown that a wide range of cellulosic source materials can be dissolved up to 3 wt.% cellulose content within comparatively short dissolution time [36].…”
Section: Phosphorylationmentioning
confidence: 61%